The relationship between treatment cost and prognosis of malignant pleural mesothelioma in Turkey - BATIREL, HASAN FEVZİ (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
BACKGROUND: Malignant pleural mesothelioma (MPM) is endemic in the population exposed to asbestos and has high health-care cost with a limited life expectancy. The aim of this study is to evaluate the relationship between cost according to treatment type and prognosis in MPM. MATERIALS AND METHODS: A total of 309 patients with MPM were evaluated. Direct medical costs were estimated as the sum of hospital bills attributed to MPM for all patients followed up from hospital application to death. Three treatment strategies were compared to each other in terms of survival and median incremental costs per month gained cost. RESULTS: The mean age of the patients was 63.2 +/- 11.2 years. The total median costs per patient and median survivals were $1838 and 5 months, $10,540 and 11 months, and $17,022 and 22 months for the best supportive care, the chemotherapy, and the multimodality groups, respectively. Factors affecting the cost of MPM were histology, treatment type, received second- and third-line chemotherapy, and number of hospitalization. CONCLUSION: MPM has a limited survival time despite treatment, and treatment cost is relatively high by prolongation of lifetime. Chemotherapy and multimodality approaches seem to be cost-effective until to be find more effective targeted therapies.
Keywords: Cost analysis of mesothelioma; direct cost of mesothelioma; mesothelioma treatment; LUNG-CANCER; PHASE-III; CISPLATIN; ASBESTOS; PNEUMONECTOMY; RADIOTHERAPY; EXPOSURE